Investigation of Soils and Bearing Capacity in Selected Construction Sites - , G. O. Adunoye; , A. O. Oyelere; , M. T. Oladepo (Archives of Current Research International, 2024)
Considering the importance of soil and foundation in the construction of engineering structures, it is important to investigate the bearing capacity of engineering soils. The purpose of this study was to examine the soils' carrying capacity in southwest Nigeria's Ife-East Local Government Area. Samples of soil were taken from a few chosen construction sites in the research region. Preliminary and geotechnical tests, including triaxia, Atterberg limits, specific gravity, natural moisture content, and particle size measurement, were performed on the soil samples using standard protocol. The bearing capacity of the soil samples was computed for different footing types (circular. square and strip footings) using Terzaghi’s bearing capacity equations. Results showed that all the soils fell into A-2-4 group, according to American Association of State Highway and Transportation Officials (AASHTO) classification standard. Also, using Unified Soil Classification System (USCS), it was observed that 75 % of the samples were well-graded sand (SW) and 25 % were poorly graded sand (SP). For square footing, the bearing capacity values ranged from 269.12 KN/m2 to 3340.85 KN/m2; for circular footings, the values ranged from 267.90 KN/m2 to 3313.47 KN/m2; and for strip footings, the values ranged from 221.58 KN/m2 to 2700.54 KN/m2. It was concluded that all the tested samples were c-ɸ soils, and all the soils could be described as excellent to good foundation materials. The study confirms the fact that the values of bearing capacity are influenced by the nature of foundation soil and shape. and circular footing was found to have intermediate magnitude in all cases.